advertisement

Solving a system of equations using Substitution 1. Solve one equation for one of the variables (this means Get one variable by itself on one side of the equal sign. 2. In the other equation, find the “first name” variable Substitute the “last name” expression into it. 3. Solve the resulting equation. (You should have Only one variable and not two anymore.) 4. Get the other variable by going back to the “shirt” equation and substitute your new answer in for the variable. 5. Frame your answer. 𝑦 = 3𝑥 𝑥 + 𝑦 = −32 𝑥 + 3𝑥 = −32 4𝑥 = −32 𝑥 = −8 𝑦 = 3𝑥